Evaluación de las prácticas verdes y su influencia en el capital de marca en restaurantes de la ciudad de Portoviejo - Alcívar Veléz, Miguel Francisco (2019)
The objective of this research was to carry out the evaluation of green practices and their influence on brand equity in restaurants in the city of Portoviejo, to carry out the research, three methodological phases were carried out. variables about green practices and brand equity, through an exhaustive bibliographic review we could identify the variables under study which are: in the first variable purchases (food supply) and brand capital, the second variable environment and green equipment and brand awareness, the third variable training of customers and employees and brand loyalty, the fourth variable menu planning and cooking with perceived quality, the fifth variable cleaning (cleaning and ecological post-treatment) with brand image and the latest variable benefits (corporate social responsibility) and green brand image. In the second phase, the current state of the variables under study was determined by applying a structured ad hoc survey with a Likert scale to a sample of restaurants in the city of Portoviejo, analyzing the results obtained through the SPSS program. And to carry out the last phase, the determination of the green practices on the brand capital was carried out, which resulted in an inverse correlation, since the Pearson scale interpretation indicates a low negative influence, which means that in the Restaurants in the city of Portoviejo do not establish green practices in restaurants to make the brand have greater impact on customers.